Detection of mosaics in hemophilia A by deep Ion Torrent sequencing and droplet digital PCR. Issue 7 (7th September 2020) - Manderstedt, Eric; Nilsson, Rosanna; Ljung, Rolf; Lind‐Halldén, Christina; Astermark, Jan; Halldén, Christer
Abstract: Background: The occurrence of mosaicism in hemophilia A (HA) has been investigated in several studies using different detection methods. Objectives: To characterize and compare the ability of AmpliSeq/Ion Torrent sequencing and droplet digital polymerase chain reaction (ddPCR) for mosaic detection in HA. Methods: Ion Torrent sequencing and ddPCR were used to analyze 20 healthy males and 16 mothers of sporadic HA patients. Results: An error‐rate map over all coding positions and all positions reported as mutated in the F8 ‐specific mutation database was produced. The sequencing produced a mean read depth of >1500X where >97% of positions were covered by >100 reads. Higher error frequencies were observed in positions with A or T as reference allele and in positions surrounded on both sides with C or G. Seventeen of 9319 positions had a mean substitution error frequency >1%. The ability to identify low‐level mosaicism was determined primarily by read depth and error rate of each specific position. Limit of detection (LOD) was <1% for 97% of positions with substitutions and 90% of indel positions. The positions with LOD >1% require repeated testing and mononucleotide repeats with more than four repeat units need an alternative analysis strategy. Mosaicism was detected in 1 of 16 mothers and confirmed using ddPCR. Conclusions: Deep sequencing using an AmpliSeq/Ion Torrent strategy allows for simultaneous identification of disease‐causing mutations in patients and mosaicism in mothers. ddPCR has high sensitivity but is hampered by the need for mutation‐specific design.